Factors Associated With Participation of Pregnant Women In Examination VCT (Voluntary Counseling And Testing) - Bunga Tiara Carolin; Dayan Hisni; Farida Afif (Health and Technology Journal (HTechJ), 2023)
HIV/AIDS has become a big scary enemy in Indonesia. The incidence of HIV/AIDS in pregnant women also makes it difficult to achieve the 2015-2019 National Medium Term Development Plan targets in the health sector at 3 points at once, namely maternal mortality, infant mortality and the prevalence of HIV cases. The Voluntary Counseling Testing (VCT) strategy is the core of all efforts to prevent and control HIV/AIDS in the world. The aim to Factors Associated With Participation of Pregnant Women In Examination VCT. The research design is an analytic method with a cross sectional study approach. The population in this study were all pregnant women who had Antenatal Care. The sampling technique used in this study is to use total sampling technique. Data analysis used univariate and bivariate analysis with the chi square statistical test. The result in this study there were 10.0% pregnant women who did not perform VCT examinations, 70% pregnant women who had good knowledge, 80% pregnant women who received support from their husbands, 82.5% pregnant women who get the role of health workers in a good category, 30% pregnant women who have a long distance from the place of health services. There is a significant relationship between knowledge (0.001), attitude (0.000), husband's support (0.000), the role of officers ((0.001) and the distance to HIV VCT examination in pregnant women. The conclusion is that many pregnant women are aware of the importance of the VCT test which can be seen in the number of pregnant women who have done the test.